EFFECT OF ASIATIC ACID ISOLATE ON DECREASING REACTIVE OXYGEN SPECIES (ROS) LEVELS IN MICE REVERSIBLE PULPITIS - shella indri novianty; Arlina Nurhapsari; Anitalia Sukma Permata Sari (Jurnal Medali, 2022)
Background: Pulpitis is a form of pulp inflammation that occurs due to the response of vascular connective tissue to a trauma or continuation of caries. During inflammation the release of Tumor Necrosis Factor Alpha (TNF-) will regulate excess ROS. Reactive Oxygen Species (ROS) can damage cellular lipids that cause oxidative stress, cell or tissue damage in mice caused by ROS to be seen with malondhydehyde biomarker (MDA) donors. Asiatic acid is a natural antioxidant that is able to neutralize free radicals by suppressing oxidative stress. This study aims to determine the effect of asiatic acid isolates on the reduction of ROS levels in reversible pulpitis mouse models.Method: This type of research is an experimental laboratory in vivo, conducted by making pulpitis on the right and left teeth of the right and left jaws of 24 male Wistar rats who were treated in the form of a control group, Asiatic Acid 0.5%, 1% and 2%, then examined using elisa sandwich method Result: The One way anova test showed that the highest mean rank was the control group and the lowest was the Asiatic Acid group of 1%. The p value < 0.05, there was a significant difference in the concentration of Asiatic Acid isolates against the significant reduction in ROS levels in reversible pulpitis between the four groups. Post Hoc LSD (Least Significant Difference test in between control groups and 1%, 0.5% and 1% group, and 1% and 2% groups obtained p < 0.05 which means there is a significant difference in reactive oxygen species (ROS) levels in reversible pulpitis between the two groups.Conclusion: Asiatic Acid was able to reduce the amount of Reactive Oxygen Species (ROS) as seen from the parameters of Malondialdehyde antibodies (MDA) in male wistar mice that developed reversible pulpitis